Sistem Pakar untuk Mendiagnosis Gangguan Tidur Menggunakan Metode Dempster Shafer - Ivo Dwi Ananda; Rahmad Kurniawan; Novi Yanti; Fitri Insani (Fakultas Teknologi Informasi Universitas Merdeka Pasuruan, 2021)
Poor quality of sleep can cause psychological and physiological health problems. Estimated from 238,452 million people in Indonesia every year, about 67% elderly people reported having trouble sleeping. With a prevalence of 10% or about 28 million people suffering from sleep disorders. This makes Indonesia has the highest number of sleep disorders in Asia. The cases of sleep disorders increased during the Covid-19 pandemic by 23.87% in general public and by 36.53% in medical personnel. This study aims to build a system that can diagnose sleep disorders like an expert. This study employed the Dempster Shafer method with 25 symptoms and four types of sleep disorders. The Dempster Shafer method is a commonly applied technique which is combining evidence in uncertainty cases. The experimental testing based on the validation of the results of the system diagnosis with expert diagnosis, the percentage of test accuracy is 90%. It can be concluded that the system potentially be used for early sleep disorder diagnosis.Keywords—expert system, dempster shafer, sleep disorders, sleep quality, uncertainty.